The changing face of cyber attacks - Chang, Emily; Bloomberg News (Firm) (New York : Bloomberg, 2013)
Bloomberg's Jordan Robertson reports on denial of service and cyber attacks. He speaks on Bloomberg Television's 'Bloomberg West.'
Title from resource description page (viewed Apr. 28, 2014).
In English.
Keywords: Computer crimes; Cyberspace -- Security measures; Criminalité informatique; Cyberspace -- Security measures; Computer crimes; Television news programs; Television news programs; Téléjournaux.